Efeito do alagamento nas respostas morfofisiológicas em porta - enxertos de cacaueiro (Theobroma cacao L.) - Pinto, Maria Luiza Pereira Barbosa (2020)
The response of cacao to the reduction of oxygen in the soil and recovery after suspension of stress is associated with the plasticity capacity of each genotype, however studies that evaluate the influence of the rootstock on the response to stress are